The use of creatine in strength training and improving physical performance (Research, Society and Development, 2021)
Introduction: Resistance training, also known as strength training, has become one of the most popular forms of exercise to improve the physical fitness and conditioning of athletes. Creatine supplementation has been the main choice among athletes with characteristics of maximum strength, explosiveness and speed. General Objective: Understand the effects of creatine in strength training and physical conditioning through the specific objectives of the research, which are: to characterize creatine and its natural sources; emphasize the importance of the nutritionist in prescribing supplements in the practice of strength training; to point out the effects of creatine supplementation on strength training and on improving physical fitness. In fact, when combined with creatine supplementation, strength or resistance training has the greatest benefit in increasing body mass, maximal strength, increasing weight lifting capacity, increasing fat-free mass, and increasing myofibrillar proteins. Methodology: This is a literature review with a descriptive approach. Results and Discussion: For data analysis, a qualitative approach was used, where the application of this method considers that there is a dynamic relationship between the real world and the research object, which cannot be translated into numbers. The selected data were selected in the form of descriptive text, bringing together all selected authors on the research topic. Conclusion: Through the development of this study, it was possible to demonstrate through the literature, the possible positive effects of creatine supplementation manifested as a future and favorable field of study.